Down-Regulated Exosomal MicroRNA-221 – 3p Derived From Senescent Mesenchymal Stem Cells Impairs Heart Repair - Sun, Ling; Zhu, Wenwu; Zhao, Pengcheng; Zhang, Jian; Lu, Yao; Zhu, Yeqian; Zhao, Wei; Liu, Yaowu; Chen, Qiushi; Zhang, Fengxiang (Frontiers in Cell and Developmental Biology, 2020)
The composition and biological activity of donor cells is largely determined by the exosomes they secrete. In this study, we isolated exosomes from young (Young-Exo) and aged (Age-Exo) mesenchymal stem cells (MSCs) and compared their regeneration activity. Young Exo MSCs were more efficient than Aged-Exo at promoting the formation of endothelial tube, reducing fibrosis, and inhibiting apoptosis of cardiomyocytes in vitro; and improving cardiac structure and function in vivo in the hearts of rats following myocardial infarction (MI). MicroRNA sequencing and polymerase chain reaction (PCR) analysis revealed that miR-221-3p was significantly down-regulated in Aged-Exo. The aged MSCs were rejuvenated and their reparative cardiac ability restored when miR-221-3p was overexpressed in Aged-Exo. The protective effect was lost when miR-221-3p expression was knocked down in Young-Exo. These effects of miR-221-3p were achieved through enhancing Akt kinase activity by inhibiting phosphatase and tensin homolog (PTEN). In conclusion, exosomal miR-221-3p secreted from Aged MSCs attenuated the function of angiogenesis and promoted survival of cardiomyocytes. Up-regulation of miR-221-3p in aged MSCs improved their ability of angiogenesis, migration and proliferation, and suppressed apoptosis via the PTEN/Akt pathway.